Shift work and burnout among health care workers - A. Wisetborisut (2018)
Background: Burnout, defined as a syndrome derived from prolonged exposure to stressors at work, is often seen in health care workers. Shift work is considered one of the occupational risks for burnout in health care workers. Aims: To identify and describe the association between shift work and burnout among health care workers. Methods: A cross-sectional study of health care workers in Chiang Mai University Hospital, Thailand. Data were collected via an online self-answered questionnaire and included details of shift work and burnout. Burnout was measured by the Maslach Burnout Inventory (MBI). Results: Two thousand seven hundred and seventy two health care workers participated, a 52% response rate. Burnout was found more frequently among shift workers than those who did not work shifts (adjusted odds ratio [aOR] 1.4, 95% confidence interval [CI] : 1.0-1.9). Among shift workers, over 10 years of being a shift worker was associated with increasing burnout (aOR 1.7, 95% CI: 1.2-2.6) and having 6-8 sleeping hours per day was associated with having less burnout (aOR 0.7, 95% CI: 0.5-0.9). Nurses who had at least 8 days off per month had lower odds of burnout compared with those with fewer than 8 days off (aOR 0.6, 95% CI: 0.5-0.8). Conclusions: Shift work was associated with burnout in this sample. Increased years of work as a shift worker were associated with more frequent burnout. Adequate sleeping hours and days off were found to be possible protective factors. Policies on shift work should take into account the potential of such work for contributing towards increasing burnout. © The Author 2014. Published by Oxford University Press on behalf of the Society of Occupational Medicine. All rights reserved.